1976
DOI: 10.1136/gut.17.3.228
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of echography in the diagnosis of pancreatic disease.

Abstract: Echography is a fairly recent addition to the methods available for the diagnosis of pancreatic disease and as little work has been reported in this field its diagnostic value has yet to be fully evaluated.The normal pancreas is not always well visualized by echography and it is often difficult to distinguish from the surrounding structure; on the other hand, the diseased pancreas, which is usually enlarged and structurally altered, gives a well-defined picture which may be of great assistance in diagnosis (En… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1981
1981
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 7 publications
(9 reference statements)
0
4
0
Order By: Relevance
“…The popularity of ultrasonography (US) has meant that it has played a primary role in detecting such tumors. 1 However, US is still limited in its ability to detect such small-sized tumors located in the tail of the pancreas. In nonfunctioning tumors, diagnosis is usually not made until the tumor has become enlarged, since symptoms are not evident.…”
mentioning
confidence: 99%
“…The popularity of ultrasonography (US) has meant that it has played a primary role in detecting such tumors. 1 However, US is still limited in its ability to detect such small-sized tumors located in the tail of the pancreas. In nonfunctioning tumors, diagnosis is usually not made until the tumor has become enlarged, since symptoms are not evident.…”
mentioning
confidence: 99%
“…To our knowledge, this is the only report evaluating the performance of US compared to EUS. With the exception of one study by Lutz & Al which was never reproduced [8], our present and recent [11] evaluations represent improvements of the diagnostic performance of US compared to older studies [3][4][5][6][7].…”
Section: Discussionmentioning
confidence: 52%
“…Transabdominal ultrasonography (US) is the first-line imaging method in the workup of chronic pancreatitis (CP) [1,2]. Previous studies demonstrated varying degrees of diagnostic accuracy of the modality with sensitivities of 40-95 % and specificities of 66-98 % [3][4][5][6][7][8]. Advances in ultrasound technology may have improved diagnostic performance [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…The first attention for research and technique development was focused on the evaluation of pancreatic disorders. [ 1 ] In the subsequent decades, the main areas of interest were represented by pancreatic neoplastic and inflammatory diseases, mucosal and subepithelial tumors of the gastrointestinal (GI) wall, and extrahepatic biliary tree disorders ( i.e ., obstruction, jaundice, biliary tree stones, and tumors). [ 2 ] Since the introduction of curvilinear array echoendoscopes in 90's, EUS was not only considered a diagnostic technique for identification and staging but also for interventional approaches, such as tissue acquisition and therapeutic maneuvers.…”
Section: Introductionmentioning
confidence: 99%